Balaenoptera acutorostrata Lacepede 1804 - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
334. Balaenoptera acutorostrata Lacépède, 1804 Common name: Common Minke Whale Myanmar name: Distribution: Worldwide distribution from arctic to tropical waters. In Myanmar, possibly distributed in the Andaman Sea and Bay of Bengal. Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on page 189, DOI:10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939